Analysis of Communitybased Aspects as Social Education For Successful Management of Cultural Tourism Objects After the Covid 19 Pandemic in Bireuen Regency, Aceh Province - Husen, M. Jamil; Rahmi Novalita, Rahmi Novalita; Wahyuni, Sri; Sri Wahyuni (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
This study seeks to examine community-based aspects as social education for the success of managing cultural tourism objects after the COVID-19 pandemic. The type of research used is descriptive qualitative research. Informants in this study are key informants, namely managers of cultural tourism objects, geucik, visitors and the community around cultural tourism objects. Informant retrieval technique using snowball sampling technique. Data collection techniques include observation, interviews, and documentation. Data analysis uses data reduction, data display, and drawing conclusions. The results of the study found that the community-based aspect as a successful tourism object management strongly supports the sustainability of tourism in Bireuen district both in terms of the role of outsiders, justice, conflict resolution, empowerment, knowledge and awareness, and sustainable use. In addition, the need for collaboration in the development of cultural tourism objects that are effective in advancing a common vision in the development of cultural tourism objects in a sustainable manner. One of the recommendations is that the authorities should pay more attention to the implementation of better tourism policies and services and maximize the benefit of local communities.